Intervention with physical exercise in the family health unit for postmenopausal women - Chagas, Eduardo Federighi Baisi (Journal of Health Care, 2016)
Introduction: The use of physical exercise programs (PEF) in the Family Health Unit (USF) is increasingly common, but little is known about the contribution and the applicability of these programs. Objective: To evaluate the effect of a PEF developed for the conditions available at USF on pain symptoms, quality of life, and functional fitness of postmenopausal women. Methods: The sample consisted of 27 women (45-79 years old), distributed for convenience in exercise group (n=14) and without exercise (n=13). The PEF was conducted in three sessions per week, with 10 minutes of warming up, 20 minutes of located exercises, and 50 minutes of aerobic exercises (55-65% VO2max) over 12 weeks. Results: Exercise group showed significant improvement in the quality of life, but without significant interaction (p=0.104). For functional fitness, it was observed significant effect (p=0.007) of PEF only for aerobic endurance. The exercise group had reductions in pain symptoms in the neck/chest area (21.4% to 7.1%) and in the region of the lower limbs (61.5% to 50%). Conclusion: Regarding the quality of life, it is understood that many factors can influence this variable, so the results seen here do not allow excluding the possible influence of exercise on this indicator. The significant improvement in functional fitness only in aerobic endurance is mainly due to the longer time destined for aerobic activities, and the time devoted to other aspects of functional fitness is insufficient for observing significant improvements. The reduction of pain symptoms, although not significant from a statistical point of view, has significant clinical importance.